Balti pataljoni formeerimisest ja koosseisust [The Formation and Composition of the Baltic-German Battalion of the Estonian Army in the War of Independence (1918–1920)] - Õismaa, Siim (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2011)
In the course of the Estonian War of Independence (1918–1920), several ethnic units were established within the Estonian armed forces. For instance, the Ingerian Battalion was recruited from amongst the Finns living in the territory between Narva and St. Petersburg; the Kachanov Battalion from amongst the Russians of Kachanov Parish in North-Eastern Latvia and Laura Parish in South-Eastern Estonia, both of which are now part of the Russian Federation. The Northern-Latvian Brigade consisted of local Latvians and Northern-Latvian draftees, as well as Latvian prisoners- of-war. And Estonian Baltic-Germans, having concluded an appropriate agreement with the Estonian government, established the voluntary Baltic Battalion (in German, also called a regiment – Baltenregiment).The Baltic Battalion was one of the more unique units in the Estonian armed forces during the War of Independence. Th e agreement for establishing the unit was concluded on 26 November 1918, between the Estonian Temporary Government and the representatives of the Baltic-German associations and societies, as well as Knigthoods. The Battalion “for the protection of the homeland, private individuals, and personal property,” was established upon the same principles as the rest of the units of the Estonian armed forces. The Estonian Temporary Government was to pay the wages and supply the equipment. At the negotiations, the Temporary Government was represented by Prime Minister and Minister of War Konstatin Päts, and the Baltic-Germans by Baron Georg Stackelberg, as well as by lawyers Max Bock and Harry Koch (minister for German ethnic affairs in the Estonian Government of 1918–1919). The leading figure of the Knighthood of Estonia, Baron Eduard Dellinghausen, also participated in the meeting.The Knighthoods of Estonia, Livonia, Courland, and Saaremaa were official public corporations, the members of which were, mostly, Baltic-German owners of manors. Until the collapse of Imperial Russia, in 1917–1918, the Knighthoods fulfilled the task of local governments in rural areas.But the formation of Baltic-German units had begun even before the agreement was concluded. In the city of Rakvere, the 5th Estonian Regiment had established the Baltic-German Mounted Machine-Gun Commando that was led by Colonel Konstantin von Weiss, the later commander of the Baltic Battalion. In the city of Viljandi, a Baltic-German militia (Heimatschutz) squad had been established, led by Captain Viktor von zur Mühlen, later, the chief of staff of the Battalion.At the end of November, a Baltic-German militia unit was also established in Estonia’s college town of Tartu. On 18 December 1918, the Viljandi and Tartu militia squads were combined to form the Tartu Baltic Battalion, under the command of Captain Viktor von zur Mühlen. The establishing of the Baltic Battalion was made easier by the support provided by the departing Imperial German forces2 and Baltic-German activists. Some German nationals even volunteered and joined the Battalion.On 1 January 1919, the Rakvere Mounted Machine-Gun Commando was merged with the Tartu Baltic Battalion. This was the actual birth of the Baltic Battalion, or Baltenregiment, itself. With the joining of additional volunteers, the Reserve Company of the Baltic Battalion was established in Tallinn, on 3 January 1919, commanded by Colonel Baron Theodor Stackelberg. The Baltic Battalion consisted only of volunteers, and was never reinforced with draftees. The men serving in the unit were of very different backgrounds. 10–15% of them were noblemen and manor owners. Most of the enlisted men were from the middle class, with the majority being Baltic-Germans, although there were some Estonians among them also.Later, in May 1919, a Russian Company, under the leadership of Baltic- German officers, was also added to the Battalion. The Baltic Battalion differed, structurally, from other Estonian Army battalions. In a usual Estonian single battalion, there were four rifle companies, a machine-gun detachment, a mounted and infantry reconnaissance commando, as well as various rear backup units. A battalion was to consist of 1,040 men, with 675 of them being combat personnel.But, in reality, there were never that many men in any Estonian battalion. Unlike other Estonian Army battalions, the Baltic Battalion also encompassed a cavalry troop, a mounted machine-gun commando, and an artillery battery. Administratively, the cavalry troop and artillery battery actually were not part of the Baltic Battalion, having the status of single independent units.The other big difference, when compared to other units in the Estonian Army, was the number of officers. In the course of the War of Independence, a total of 253 officers served in the Baltic Battalion. Baltic-Germans usually tended to be part of the upper crust of the population in Estonia. A large part of the men were secondary school, college, or even military academy graduates, so that many of them were reserve or active military officers. And due to the First World War, which had just ended, a majority of the reserve officers had acquired combat experience while serving in the Russian armed forces. And there were even those Baltic-Germans who had served in the German military. Since there was actually a surplus of officers in the Baltic Battalion, the majority of them served as non-commissioned officers, or even as enlisted men. For instance, in the cavalry troop, there were, in October 1919, 32 officers, with only six of them actually serving as such. At the same time, in the Estonian Army’s 7th Infantry Regiment, there were, instead of the 70 offi cers called for, only 45 to 50.On 22 February 1919, one of the most unique units of the Estonian War of Independence, or in the annals of military history generally, was established – the Baltic Battalion’s armed iceboat flotilla on Lake Peipus, which consisted of fi ve ice sailing vessels armed with machine-guns. The Baltic Battalion participated in the driving out, from Estonian territory, of the Red Army, in December 1918. Thereafter, the Battalion  fought on the Narva front, in North-Eastern Estonia, serving, temporarily, under the White Russian North-Western Army of General Nikolai Yudenich.By the end of the War of Independence, the Baltic Battalion consisted of four infantry companies, a machine-gun company, a cavalry troop, an artillery battery, a mounted machine-gun commando, various rear backup and staff units, as well as a reserve company in Tallinn. On 3 January 1920, there were 487 men, 24 machine-guns, and three artillery pieces at the front. In the reserve unit, in Tallinn, there were 200 men. In the course of the War, 1,350 individuals served in the Battalion, of whom, 71 men and women were killed, or died of wounds or disease, and 118 were wounded.Members of the Baltic Battalion were awarded five Freedom Crosses. Although the existence of the Baltic Battalion brought forth, especially during the Landeswehr conflict, temporary hostility from among some of the Estonian military leadership, as well as the civilian population, the Baltic-German unit was not disbanded. But, the Estonian Temporary Government, nevertheless, disbanded the Defence League’s 43rd Tallinn Defence Battalion, which consisted of Baltic-Germans residing in Tallinn. But, after the end of the Landeswehr conflict, relationships between the two nationalities normalized. And eventually, the Baltic Battalion’s service in the Estonian War of Independence, within the ranks of the Estonian armed forces, helped to make the country’s former upper class, more or less, palatable for the native Estonians.At any rate, during the inter-war period, the relationship between the Baltic-Germans and the native population in Estonia can be regarded as having been better than in Latvia. One reason for this is the fact that the Baltic-German population in Estonia was smaller than in neighbouring Latvia. The other being the fact that, in Estonia, the Baltic-Germans served and fought loyally in the Estonian armed forces, while in Latvia, the Baltic-German Landeswehr, although, formally, part of the Latvian armed forces, participated in a military operation that, in 1919, for some time, toppled the Latvian legal government from power, and was in direct armed conflict with Estonian and Latvian units.The Landeswehr conflict – an extended armed encounter between the Estonian and Latvian armed forces and German units (a German Freikorps known as the Iron Division, along with the Landeswehr, a Baltic-German unit recruited in Livonia and Courland, under the overall command of General Count Rüdiger von der Goltz) ostensibly also fighting against the Red Army, which took place in Northern Latvia in June and July 1919.The Defence League – the Kaitseliit, the popular Estonian voluntary paramilitary civil defence organization that functions to this day.